Dental Arch Dimension Changes Following Prematurely Extracted Deciduous Molars (Mustansiria Dental Journal, 2018)
The aim was to assess the vertical and horizontal dimensional changes in themaxillary and mandibular dental arches after the unilateral premature loss ofdeciduous molars. Methods: The sample consist of 100 child between 8-9 years of agewith unilateral loss of first or second deciduous molars, either in the maxillary ormandibular arches, Study casts were made and measurements conducted on the Autosketch program on the computer , The data obtained was subjected to statisticalanalysis. The Results of the study showed that when comparing the mean values ofthe loss groups with the control group a statistically significant difference in themaxillary (A) distance after the premature loss of first or second deciduous molars,however a high significant difference statistically in the (ML) distance recorded afterthe premature loss of maxillary second deciduous molar ,while in the mandibular archa statistically high significant difference observed in most of the vertical andhorizontal distances following premature loss of second deciduous molar.Conclusions: The major effect on the dental arch length and width following thepremature loss of the deciduous molars, indicating the need for fitting the spacemaintainers' appliances as soon as the extraction is the final decision to the dentist.